2016
DOI: 10.1182/blood-2015-06-649434
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA enrichment in platelets is a signature of transcriptome degradation

Abstract: Key Points• Circular RNAs are hugely enriched in platelets compared with nucleated cell types.• Lack of enrichment in megakaryocte progenitors implicates degradation of platelet linear RNAs.In platelets, splicing and translation occur in the absence of a nucleus. However, the integrity and stability of mRNAs derived from megakaryocyte progenitor cells remain poorly quantified on a transcriptome-wide level. As circular RNAs (circRNAs) are resistant to degradation by exonucleases, their abundance relative to lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
178
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 63 publications
10
178
0
Order By: Relevance
“…Strikingly, in platelets, a large set of circular isoforms (70% in resting, 66% in activated platelets) are predominantly expressed, and 95% of these abundant circRNAs are identical in resting and activated platelets. These results are consistent with the previous study by Alhasan et al [20], which showed that circRNAs are highly enriched in platelets and, in addition, that for some genes only the circular isoform was detected; especially the enrichment of back-splice junctions detected is clearly in line with our finding, when comparing the circular/linear-junction reads in the different hematopoietic cell types (see Figure 1(a)).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Strikingly, in platelets, a large set of circular isoforms (70% in resting, 66% in activated platelets) are predominantly expressed, and 95% of these abundant circRNAs are identical in resting and activated platelets. These results are consistent with the previous study by Alhasan et al [20], which showed that circRNAs are highly enriched in platelets and, in addition, that for some genes only the circular isoform was detected; especially the enrichment of back-splice junctions detected is clearly in line with our finding, when comparing the circular/linear-junction reads in the different hematopoietic cell types (see Figure 1(a)).…”
Section: Resultssupporting
confidence: 94%
“…Moreover, the ratio between the linear spliced mRNA and the circular isoform is very often shifted towards the circular form, which is more stable than linear RNA [20]. Therefore, Alhasan et al had explained this phenomenon by differential degradation of cellular platelet RNA [20].…”
Section: Resultsmentioning
confidence: 99%
“…, testes (Liang et al 2017b), peripheral whole blood 62 (Memczak et al 2015), peripheral blood mononucleotide cells (Qian et al 2018), platelets 63 (Alhasan et al 2016), and exosomes (Li et al 2015a). CircRNAs have also been related to the 64 development of the fetal human brain (Szabo et al 2015), mouse brain (You et al 2015), fetal 65 porcine brain (Veno et al 2015), and Drosophila neural systems (Westholm et al 2014).…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Because platelets lack the ability to synthesize new messenger RNA (mRNA) transcripts or assemble new ribosomes, the abundance of MK-derived RNA in platelets gradually declines over several days. 10,12,13 This bulk decrease in RNA principally reflects the clearance of ribosomes (and the constituent ribosomal RNA [rRNA]), similar to the maturation process that occurs in reticulocytes during terminal differentiation. [14][15][16] The mechanisms of mRNA and ribosome decay in platelets are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Given the documented clearance of RNA by platelets during the first several days of circulation, 3,10,12 it seems likely that platelet protein synthesis primarily occurs within a few days of release from the MK. 11,13 However, some evidence exists for translation in older The data used in this article have been deposited in the National Center for Biotechnology Information Gene Expression Omnibus database (accession number GSE94384).…”
Section: Introductionmentioning
confidence: 99%